Effect of polyunsaturated fatty acids on the fecundity of the Amazon river prawn Macrobrachium amazonicum (Heller, 1862) - Ribeiro, Karina; Franceschini-Vicentini, Irene Bastos [UNESP]; Papa, Luciene Patrici [UNESP]; New, Michael B.; Valenti, Wagner Cotroni [UNESP] (Wiley-Blackwell, 2012)
Effects of the ratio of dietary fatty acids, namely n-3 (mainly long chain polyunsaturated LC-PUFA) to n-6 PUFA on the fecundity of Macrobrachium amazonicum were evaluated. In T1, the diet had equal and low levels of dietary n-3 and n-6 fatty acids (6 mg g(-1)). In T2, the concentration of n-3 (6 mg g(-1)) was a half of the concentration of the n-6 (12 mg g(-1)), and in T3, the diet had equal and high concentrations of n-3 and n-6 (12 mg g(-1)). Females with ovaries in stages I, III and V were collected. Higher gonadosomatic index (GSI) (6.89%) was observed in females in ovarian stage V than at other ovarian stages; however, the hepatosomatic index (HIS) showed high values in all females with ovaries in the stage III. A ratio of 1:2 n-3:n-6 fatty acids increased the GSI of mature females and the number of eggs spawned. Raising the level of both n-3 and n-6 fatty acids from 0.6% to 1.2% of the diet did not produce any effect on the GSI or on fecundity, suggesting that the ratio is more important than the absolute value of these two families of fatty acids.
Keywords: aquaculture; Macrobrachium amazonicum; freshwater prawns; practical diets; fatty acids and fecundity